Hafnium oxide—A promising addition to the zoo of passivation layers for silicon solar cells? - Jan Schmidt; Michael Winter; Dag Luis Günther; Floor Souren; Jons Bolding; Hindrik de Vries (AIP Advances)
Hafnium oxide (HfO2) has been known for a long time as a high-κ dielectric in silicon microelectronics. Recently, it has found its way into silicon photovoltaics, where it is applied as the surface-passivating dielectric. In this study, we examine the surface passivation quality of atomic-layer-deposited HfO2 layers on n-type silicon surfaces. We measure effective lifetimes of above 5 ms, corresponding to surface recombination velocities (SRVs) between 1 and 2 cm/s, which are among the lowest SRVs reported to date for HfO2-passivated silicon surfaces. We examine the passivation mechanism of the HfO2 by means of corona charging experiments, which reveal a significantly lower negative fixed charge density of HfO2 compared to Al2O3 and a lower interface state density. Hence, field-effect passivation is less pronounced and interface passivation is more pronounced for HfO2 compared to Al2O3. As an important consequence, for HfO2, no inversion layer formation occurs on n-type silicon surfaces in contrast to Al2O3, which makes HfO2 better suited than Al2O3 for edge passivation or rear passivation of “interdigitated back contact” cells on n-type silicon. The firing stability of the HfO2 passivation is found to improve by adding a hydrogen-rich silicon nitride (SiNx) capping layer. For HfO2/SiNx stacks with only 3 nm of HfO2, implied one-sun open-circuit voltages of 740 mV are attained after high-temperature firing in a conveyor-belt furnace, as used for the metal contact formation in industrial silicon solar cells.